From Careers Adviser to Personal Adviser: Emotion, Ethics, Politics and Learning in a Disrupted Community of Practice - Helen Colley (Adult Education Research Conference, 2009)
This paper discusses recent policy reforms in career guidance for young people in England. It offers a case study of disruption to an established community of practice; presents evidence of its emotional, ethical and political effects; considers the implications for workplace learning and reconsiders theoretical conceptualisations of ‘communities of practice’.